Sustainability balanced scorecard for a brazilian agricultural and livestock company - Araújo, Lindiana (2020)
The agricultural sector in Brazil has a noticeable impact on its wealth and a significant effect on sustainability. This study presents the corporate sustainability management through the integration of social and environmental issues in the traditional Balanced Scorecard, that is, through a Sustainability Balanced Scorecard (SBSC). It establishes causal relationships between economic, social and environmental perspectives, and highlights its potential impacts. This study relays on the Brazilian company with the largest amount of agricultural land. This company acquires, develop, exploit and commercialize rural properties that are suitable for agriculture. The main purpose of this paper is to study the company and to propose an SBSC. We present a qualitative case study based on interviews and on documental analysis. We conclude that, through this framework, sustainability can be aligned with the strategic management of the company. The implementation of an SBSC provides organizational benefits and must take into consideration the peculiarities of each organization.